Market alternatives for smallholder farmers in food security initiatives: Lessons from the Brazilian Food Acquisition Programme - Danuta Chmielewska; Darana Souza (International Policy Centre for Inclusive Growth (IPC-IG), 2010)
[Introduction ...] This study looks at the outcomes of the latter programme for farmers' market access. Our goal is to identify and discuss key elements that could be explored in further international debate, sharing lessons learned from programmes that combine supporting food production (through trading opportunities targeted at or open to smallholder farmers) with giving vulnerable populations access to food. This is the first study in a series to be conducted by the International Policy Centre for Inclusive Growth (IPC-IG) to compare experiences of this kind. The next phases of the research will discuss India's PDS and WFP's Purchase for Progress.
Keywords: 330